Laboratory evaluation of attract-and-kill formulations against the Indianmeal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae) - Campos, Manuel; Phillips, Thomas W. (My University, 2013)
Pheromone-based population suppression methods for stored-product insects can reduce or eliminate application of chemical insecticides near finished food products. The responses of adult male Indianmeal moth males (IMM), Plodia interpunctella (Hübner), to the attract-and-kill formulations of a gel, a flat wax panel, and a plastic cylinder device, mixed or sprayed with the pyrethroid insecticides permethrin, cyfluthrin, or organically compliant natural pyrethrin, combined with the synthetic female sex pheromone (Z,E) -9,12 tetradecadienyl acetate, were evaluated in a laboratory wind tunnel. The wax panel and cylinder, which utilized controlled-release pheromone lures, were more attractive to IMM males over the course of an eight-week aging period than was the gel, which had the pheromone incorporated into the gel matrix. The contact time for responding males was longer on the wax panel and plastic cylinder than on the gel formulation. The percentage of mortality of males was higher with wax panels formulated with cyfluthrin at 6.0% AI, permethrin at 6.0% AI and the cylinder formulated with cyfluthrin at 2.0% AI, compared to the gel over the eight-week study. These same formulations had the greatest impact on egg-laying by females paired with treated males and on the percent of eggs that hatched. Of all the attract-and-kill formulations tested, the most promising for field applications to suppress IMM pest populations was the wax panel containing 6.0% AI of either cyfluthrin or permethrin.
Citation: Campos, M., & Phillips, T. W. (2013). Laboratory evaluation of attract-and-kill formulations against the Indianmeal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae). Retrieved from http://krex.ksu.edu
Keywords: Wind tunnel; Attracticide; Pheromone; Stored-products; Residual insecticides